Sustainability of settlements around conservation units: the case of Parque Estadual Mata da Pimenteira in Serra Talhada/PE - Bilar, Alexsandro Bezerra Correia; Pimentel, Rejane Magalhães de Mendonça; Araújo, Maria do Socorro Bezerra de (Sustainability in Debate, 2016)
The existence of projects for the creation of settlements, originated in land reform programs and located around conservation units is a recent phenomenon in the Northeastern semi-arid region of Brazil. The creation of strategies that harmonize the Caatinga’s preservation needs with local sustainable development is a challenging mission. Aiming to investigate the sustainability of these settlements and to identify which benefits are being generated from such coexistence, the present research evaluated the sustainability of Assentamento Lajinha, which is located near Parque Estadual Mata da Pimenteira in Serra Talhada/PE. A sustainability index that examined the settlement’s environmental, social, economic and institutional dimensions was applied. Furthermore, benefits generated for both parties were analyzed. Field research and interviews with representatives from these territorial spaces were carried out. Results point out to unsatisfactory sustainability indexs on the studied dimensions, with the exception of the institutional indicators, thus characterizing a generally low sustainability framework.